AB0724 Higher likelihood of anti-tnf prescription in men vs women with ankylosing spondylitis despite similar disease burden: results from routine care at two academic rheumatology centers of usa and spain. (15th June 2017) - Blasco-Blasco, M; Castrejόn, I; Ruiz-Cantero, M; Jovaní, V; Pascual, E; Block, J; Pincus, T
Abstract : Background: Ankylosing spondylitis (AS) has been considered to be more prevalent in men compared to women. Besides, the clinical presentation in women is thought to be milder and more peripheral than in men. Some studies have suggested a higher burden of disease in women 1, 2 but others not confirm these differences 3, 4 . Objectives: To evaluate possible gender differences in men and women with AS seen in routine care at two academic rheumatology centers of the USA and Spain. Methods: Sixty one men and 30 women with AS in Spain and 61 men and 31 women in the USA completed a Multidimensional Health Assessment Questionnaire (MDHAQ). The MDHAQ includes (0–10 scores) for physical function, pain, patient global estimate (PATGL), compiled into a 0–30 RAPID3, and fatigue scores. Furthermore, demographic data, biological (anti-TNFα) and DMARD therapies, were obtained from the medical records. A comparative analysis of men and women was performed by Mann-Whitney U tests for non-parametric quantitative data (median/interquartile range), and Chi square tests for qualitative data (frequencies/percentajes). Results: We have not detected significant differences in men and women for function, pain, PATGL, or fatigue although a trend towards higher RAPID3 values was seen in females in both sites (Table). Anti-TNFα medications were prescribed more often in men than in women (81.2% vs 65.6%, in all patients p=0.02), statistically significant in Spain (82% vs 60%, p=0.02), and numerically higher in the USA (80.3% vs 71%, p=0.31). DMARD medications tend to be more prescribed in women than men in all patients (17.2% vs 23%, p=0.35) although no statistically significant. Conclusions: Men with SpA receive anti-TNFα more likely than women; although disease burden appears somewhat higher in women. This pattern is similar in both Spain and the USA, though statistically significant only in the Spanish population. Other parameters may be having weight in the management of SpA, such as radiographic signs versus peripheral manifestations. References: van der Horst-Bruinsma IE, et al. Ann Rheum Dis 2013. Ortega Castro R, et al. Reumatol Clin 2013. Gremese E, et al. Rheumatology (Oxford) 2014. Shahlaee A, et al. Clin Rheumatol 2015. Acknowledgements: University Institute for Gender Studies (University of Alicante) supported MBB. Disclosure of Interest: M. Blasco-Blasco: None declared, I. Castrejόn: None declared, M. Ruiz-Cantero: None declared, V. Jovaní: None declared, E. Pascual: None declared, J. Block: None declared, T. Pincus Shareholder of: Health Report Services, Inc.